Introduction to questionnaire data patterns using Perceptron Algorithm for lecturer improvement and development in higher education - Irwan Irwan; Rusnardi Rahmat Putra; Krismadinata Krismadinata; Nizwardi Jalinus (Universitas Negeri Padang, 2021)
This artificial neural network research article aimed to overview the current teaching process focusing on lecturer performance using the perceptron algorithm, improving the teaching process, developing the lecturer based on the perceptron algorithm's results, evaluating the speed and accuracy of the perceptron algorithm in evaluating performance lecturer and learning the rules of the perceptron algorithm in processing assessment criteria for lecturers in tertiary institutions. In this case, the perceptron algorithm was used to recognize the questionnaire data input patterns. The perceptron algorithm was trained and tested to recognize input data patterns so that this neural network could identify input data patterns from questionnaire data.